Influence of microstructural deformation mechanisms and shear strain localisations on small fatigue crack growth in ferritic stainless steel. (October 2022) - Gallo, P.; Lehto, P.; Malitckii, E.; Remes, H.
Graphical abstract: Highlights: Microstructurally small fatigue crack growth (FCG) rate is studied by DIC. FCG rate retardation is associated with shear strain localisations. Grain boundaries control interaction between strain localization and FCG. Shear strain localisations lead to formation of grain sub-structures. Intense cross slip facilitates the overcoming of the strain localisation zone. Abstract: Microstructurally small fatigue crack growth (FCG) rate in body-centred cubic (BCC) ferritic stainless steel is investigated by using a novel domain misorientation approach for EBSD microstructural deformation analyses, in conjunction with in situ digital imaging correlation (DIC). The DIC analyses revealed that shear strain localisations occur ahead of the crack tip during propagation and correlate well with the FCG rate retardations. Grain boundaries can be found at both peaks and valleys of the FCG rate curve and alter the interaction between crack growth and shear strain localisations. At the microstructural level, the deformation is associated with the dislocation-mediated plastic deformation process, showing increased formation of grain sub-structures in the regions of the strain localisation. Consequently, material experiences local hardening causing the FCG retardation events. If the crack avoids the hardened material region through a macroscopic cross-slip mechanism, retardation is minor. On the contrary, if the crack penetrates the hardened region, retardation is significant.